DLC1 inhibits colon adenocarcinoma cell migration by promoting secretion of the neurotrophic factor MANF - Chu, Yi-Min; Xu, Ying; Zou, Xiu-Qun; Zhou, Feng-Li; Deng, Yu-Liang; Han, Yu-Tong; Li, Ji; Yang, Da-Ming; Peng, Hai-Xia (Frontiers in Oncology, 2022)
DLC1 (deleted in liver cancer-1) is downregulated or deleted in colorectal cancer (CRC) tissues and functions as a potent tumor suppressor, but the underlying molecular mechanism remains elusive. We found that the conditioned medium (CM) collected from DLC1-overexpressed SW1116 cells inhibited the migration of colon adenocarcinoma cells HCT116 and SW1116, but had no effect on proliferation, which suggested DLC1-mediated secretory components containing a specific inhibitor for colon adenocarcinoma cell migration. Analysis by mass spectrometry identified mesencephalic astrocyte-derived neurotrophic factor (MANF) as a candidate. More importantly, exogenous MANF significantly inhibited the migration of colon adenocarcinoma cells HCT116 and SW1116, but did not affect proliferation. Mechanistically, DLC1 reduced the retention of MANF in ER by competing the interaction between MANF and GRP78. Taken together, these data provided new insights into the suppressive effects of DLC1 on CRC, and revealed the potential of MANF in the treatment of CRC.